FEEDING STUDY OF TOFU WASTE FERMENTATION ALTERNATIVE IN THE BUSINESS CULTURE OF NILE TILAPIA FISH (Oreochromis niloticus) IN CILONGOK DISTRICT, BANYUMAS DISTRICT - Ganjar Wiryati ganjar (Jurnal Perikanan Unram, 2024)
This research aims to examine alternative feed made from tofu dregs to reduce production costs, especially feed costs by 10-20% in tilapia rearing businesses. In Kalisari Village, Cilongok sub-district, there is tofu dregs waste that has not been utilized. The nutritional content of tofu apas is crude protein 27.55%, fat 4.93%, crude fiber 7.11%, BETN 44.50%, Making fish food with tofu dregs can be done through a fermentation process with probiotics. This descriptive analysis method is used for qualitative data presented in the form of simple descriptions and tabulations such as tables, diagrams, graphs. The data collected is in the form of primary data and secondary data, primary data using the interview method, kuestionnaire using direct observation in the field while secondary data using literature study. The research was carried out in Cilongok District from 2 February to 2 May 2023. Based on the data analysis that has been carried out, it shows that providing alternative feed with a percentage of pellets and fermented tofu dregs (50%:50%) is 58.9% or worth Rp. 2,102,109,- (tarpaulin pool) and 59.8% or Rp. 2,181,909,- (ground pool). Then in ponds with cultivation treatment according to SNI and providing alternative feed with a percentage of pellets and fermented tofu dregs (75%:25%) of 50.2% or worth Rp. 1,475,109,- Use of fermented tofu dregs as alternative feed if converted on a scale A business with an average pool area of main actors/businesses in Cilongok District (190m2), can reduce production costs for feed production by IDR 866,805.- or 16.85%.